DETECTION AND STUDY OF LUMINESCENCE COMETARY CONTINUUM IN SPECTRA OF COMETS SCHAUMASSE (24P), SCORITCHENKO-GEORGE (C/1989 Y1) AND HALE-BOPP (C/1995 O1) - Churyumov, K. I.; Kleshchonok, V. V. (Одеські астрономічні публікації, 2017)
The authors investigated spectra of four comets with the aim to determine the real level of the non-solar origin continuum in the spectral region 350-500 nm. Spectra of three comets Schaumasse (24P), Scoritchenko-George (C/1989 Y1) and Hale-Bopp (C/1995 O1) were observed with the help of the 6-m BTA telescope and the spectrograph with the long slit at the Special Astrophysical Observatory of the Russian Academy of Sciences. Spectra of two comets Hyakutake (C/1996 B2) and Hale-Bopp (C/1995 O1) were obtained with the 1-meter Zeiss telescope and echelle- spectrometer of the SAO RAS. As a result of processing the cometary spectra we obtained: 1) For comet Schaumasse (24P) March 14-15, 1993 the level of the non-solar-origin continuum equal to 44 per cent of the sum continuum level at 430 nm; 2) For comet Scoritchenko-George (C/1989 Y1) February 27 , 1990 the level of the non-solar-origin continuum equal to 40 per cent of the sum continuum level at 387 nm, 68 per cent - at 430 nm (max) and 23 per cent - at 480 nm; 3) 2) For comet Hale-Bopp (C/1995 O1) April 17 , 1997 the level of the non-solar-origin continuum equal to 32 per cent of the sum continuum level at 397 nm and 77 per cent - at 438 nm; 4) For comet Hyakutake (C/1996 B2) March 25, 1996 the continuum of the non-solar origin was not detected. We suppose that in spectra of comets Schaumasse (24P), Scoritchenko-George (C/1989 Y1) and Hale-Bopp (C/1995 O1) we detected the real cometary continuum tied with the luminescence of the comet organic spices which are in comet dust particles.